2014
DOI: 10.1111/jiec.12084
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Greenhouse Gas Emissions of Electricity Generated from Conventionally Produced Natural Gas

Abstract: SummaryThis research provides a systematic review and harmonization of the life cycle assessment (LCA) literature of electricity generated from conventionally produced natural gas. We focus on estimates of greenhouse gases (GHGs) emitted in the life cycle of electricity generation from natural gas-fired combustion turbine (NGCT) and combined-cycle (NGCC) systems. The smaller set of LCAs of liquefied natural gas power systems and natural gas plants with carbon capture and storage were also collected, but analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 32 publications
1
60
0
5
Order By: Relevance
“…After harmonization with consistent steps as implemented here for the eight shale gas LCAs, variability decreased (e.g., −13% in interquartile range), whereas the magnitude of estimates, in aggregate, remained constant, yielding a harmonized median of 450 g CO 2 e/kWh. Thus, the results from the larger set of conventional gas LCAs considered in O'Donoughue et al (26) suggests that the harmonized median estimate of life cycle GHG emissions from shale gas used to generation electricity in a modern combined cycle facility are slightly higher (3%) than those from conventional gas used for the same purpose. Considering the expected uncertainty ranges given the breadth of assumptions used in LCAs and that the results in O'Donoughue et al could not be updated to use the AR5 methane GWP (Methods), our conclusion is that based on current evidence, life cycle GHG emissions from shale and conventional gas are not significantly different (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…After harmonization with consistent steps as implemented here for the eight shale gas LCAs, variability decreased (e.g., −13% in interquartile range), whereas the magnitude of estimates, in aggregate, remained constant, yielding a harmonized median of 450 g CO 2 e/kWh. Thus, the results from the larger set of conventional gas LCAs considered in O'Donoughue et al (26) suggests that the harmonized median estimate of life cycle GHG emissions from shale gas used to generation electricity in a modern combined cycle facility are slightly higher (3%) than those from conventional gas used for the same purpose. Considering the expected uncertainty ranges given the breadth of assumptions used in LCAs and that the results in O'Donoughue et al could not be updated to use the AR5 methane GWP (Methods), our conclusion is that based on current evidence, life cycle GHG emissions from shale and conventional gas are not significantly different (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…O'Donoughue et al (26), considering all 42 references with life cycle GHG emission estimates for conventional gas-fired combined cycle (NGCC) facilities passing screens for relevance and quality (including all shale gas LCAs considered here that published an estimate for conventional gas), found that the published range of the middle 50% of 51 estimates v is ∼410-490 g CO 2 e/kWh (full range, ∼310-680 g CO 2 e/kWh), with a median of 450 g CO 2 e/kWh. After harmonization with consistent steps as implemented here for the eight shale gas LCAs, variability decreased (e.g., −13% in interquartile range), whereas the magnitude of estimates, in aggregate, remained constant, yielding a harmonized median of 450 g CO 2 e/kWh.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Life cycle GHG emissions associated with energy consumption can be calculated using the corresponding lifecycle emissions coefficient (Equations (11) and (12)). …”
Section: Life Cycle Fossil Energy Consumption and Ghg Emissionsmentioning
confidence: 99%
“…The most frequently analyzed metrics of DG benefit include economy (net present value and internal return rate), GHG emissions, energy consumption reduction, and marginal abatement cost [10,11].…”
Section: Life-cycle Analysis As a Mainstream Evaluation Methodsmentioning
confidence: 99%